Pemanfaatan Software Tracker dalam Analisis Gerak Benda untuk Melatih Kemampuan Interpretasi Grafik Siswa: Utilization of Tracker Software in Object Motion Analysis to Train Students’ Graph Interpretation Skills - Ratnaningtyas, Delthawati Isti; Haeruddin, Haeruddin; Wahyono, Unggul; Pasaribu, Marungkil; Untara, Ketut Alit Adi; Selvianur, Selvianur; Wancenowati, Wancenowati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The ability to interpret graphs is important for students to understand the relationships between physical variables, which can lead to the discovery of concepts. There are problems with creating graphs for direct object motion analysis because the movement is fast, and there is a lack of supporting laboratory equipment, which hinders students from further interpreting the motion graphs. Tracker software can be used to determine the exact position and time of moving objects from video recordings of real events. However, students’ knowledge of Tracker use remains minimal, and their graph-interpretation skills are also underdeveloped. Based on this, the purpose of this community service activity is to guide students in analyzing object motion using Tracker software, train students’ graph-interpretation skills, and assess students’ responses to the community service activity using Tracker in object motion analysis. The implementation of this community service consists of three stages: preparation, implementation, and evaluation. Community service activities include providing materials, conducting demonstrations, completing practical assignments using Tracker in object motion experiments, interpreting graphs, and giving presentations. The conclusion from this community service is that students can use Tracker software effectively to analyze object motion experiments, that students’ graph interpretation skills are trained, and that students’ graph interpretation skills improve. Students’ responses are very good to the use of Tracker in object motion analysis to train graph interpretation skills.